The Effects of Family Financial Stress and Primary Caregivers’ Levels of Acculturation on Children’s Emotional and Behavioral Problems among Humanitarian Refugees in Australia - Yu, Linlin (Int J Environ Res Public Health, 2020)
The present study evaluated the application of the basic and extended (incorporated primary caregivers’ levels of acculturation) Family Stress Model (FSM) to understand the effect of family financial stress and primary caregivers’ levels of acculturation on children’s emotional and behavioral problems among refugees in Australia. A total of 658 refugee children aged 5–17 and their primary caregivers (n = 410) from the third wave of a nationwide longitudinal project were included in this study. We used multilevel structural equation models with bootstrapping to test the indirect effects of family financial stress and caregivers’ levels of acculturation (including English proficiency, self-sufficiency, social interaction, and self-identity) on children’s emotional and behavioral problems through caregivers’ psychological distress and parenting styles. The results showed that the extended FSM improved the model fit statistics, explaining 45.8% variation in children’s emotional and behavioral problems. Family financial stress, caregivers’ English proficiency, and self-identity had indirect effects on children’s emotional and behavioral problems through caregivers’ psychological distress and hostile parenting. The findings showed that interventions aimed at reducing caregivers’ psychological distress and negative parenting could be effective in alleviating the adverse effects of family financial stress and caregivers’ low levels of acculturation on refugee children’s mental health.